Overview of Flour Fortification Program with Iron and Folic Acid in Iran - Marjan Mahdavi-Roshan; Atena Ramezani (Mazandaran University of Medical Sciences, 2017)
Introduction and purpose: A large percentage of the world population suffers from hidden hunger, which is defined as micronutrients deficiency. Iron deficiency anemia is one of the most common complications of the micronutrients deficiency and there is a lot of effort to deal with this problem. For this purpose, this study aimed to examine the program of flour fortification with iron in Iran. Methods: The cohort, case-control, and clinical trial studies with the search strategies such as iron deficiency anemia, fortification, and micronutrients deficiency, which were conducted until 2015 were included. The data sources entailed PubMed, Ovid, Elsevier Science, Blackwell Synergy, and Google. All the selected studies were available in English and Persian. Results: In several countries, the best method for correction of the iron deficiency anemia is food fortification due to high efficacy and low adverse effects of this method. Bread is a staple food in Iran; therefore, flour fortification was performed in this country. The premix powder containing 30 ppm of iron and 1.5 ppm of folic acid was used for flour fortification. Considering the various types of wealth, the total amount of iron in flour was up to 80 to 85 ppm that may lead to iron poisoning in people with a low socio-economic status because of high bread consumption, as well as the individuals with high socio-economic status since they receive iron from the other resources. Therefore this program was stopped in several provinces due to the mentioned complication. Conclusion: Prior to the implementation of this program, it was essential to carry out abundant pilot studies to investigate the probable complications and problems of this plan. To the best of our knowledge, there is limited number of studies conducted on the adverse effects of iron fortification in Iran; therefore, further studies are recommended in this issue.